Akademski šport in življenjski slog študentov na Fakulteti za gradbeništvo in geodezijo - Golja, Aleš (Šport (Ljubljana), 2019)
Today, academic sport and the lifestyle of students, characterized by rapid changes and changing family structures, represent important components for maintaining psychophysical balance and a healthy and active life style of students during their studies. In the past, educational programs in the field of physical activity and sports at the academic level were in the form of Sport Education an integral part of curricula at University of Ljubljana members. In the time of the renewal of study programs and when adopting the Bologna reform, unfortunately, due to partial interests of the decision-makers, such programs were dropped from curricula. Consequently, the lack of educational programs in the field of sports education during the studies reduces the quality of personal life, and from the socio-economic point of view, in the long term, increases demands for health care and social costs. The aim of this article is to present a concise overview of the development of sport at the Faculty of Civil and Geodetic Engineering from its beginnings, the transformation of the organization of sport during the Bologna reform of higher education and the consequences of its effectiveness on the physical activity of students in the present day.
Keywords: Faculty of Civil and Geodetic Engineering; Fakulteta za gradbeništvo in geodezijo; lifestyle; physical education; sport; students; šport; športna vzgoja; študenti; University of Ljubljana; Univerza v Ljubljani; življenjski slog